Les villages de frontière dans le processus de territorialisation de la pampa argentine au xixe siècle - Melina Yuln (Cahiers des Amériques Latines)
Border towns were built based on the model of the regular grid or mesh. However, we can identify variations related to their status as border enclaves. Some localities from the first colonization inherited military forts ; others show exceptional cases of subdivision of rural land before the introduction of laws that promoted regular mesh plots ; others were developed in the rigid framework imposed by the territorial grid, as is the case of the territories of Patagonia. This article analyzes cases of border towns in Argentina that show a process of redefinition of territorial forms from the starting regular grid. The study uses mapping and surveying techniques as well as legal documentation. It shows that the production of the territory by the state is the result of traditional practices, normative devices and legal adjustments which together resulted in a fragmentary construction of the territory, despite the unifying effort of the state during the long process of territorialization in the nineteenth century.